Comparison of Staphylococcus Phage K with Close Phage Relatives Commonly Employed in Phage Therapeutics - Jude Ajuebor; Colin Buttimer; Sara Arroyo-Moreno; Nina Chanishvili; Emma M. Gabriel; Jim O'Mahony; Olivia McAuliffe; Horst Neve; Charles Franz; Aidan Coffey (MDPI AG, 2018)
The increase in antibiotic resistance in pathogenic bacteria is a public health danger requiring alternative treatment options, and this has led to renewed interest in phage therapy. In this respect, we describe the distinct host ranges of Staphylococcus phage K, and two other K-like phages against 23 isolates, including 21 methicillin-resistant S. aureus (MRSA) representative sequence types representing the Irish National MRSA Reference Laboratory collection. The two K-like phages were isolated from the Fersisi therapeutic phage mix from the Tbilisi Eliava Institute, and were designated B1 (vB_SauM_B1) and JA1 (vB_SauM_JA1). The sequence relatedness of B1 and JA1 to phage K was observed to be 95% and 94% respectively. In terms of host range on the 23 Staphylococcus isolates, B1 and JA1 infected 73.9% and 78.2% respectively, whereas K infected only 43.5%. Eleven open reading frames (ORFs) present in both phages B1 and JA1 but absent in phage K were identified by comparative genomic analysis. These ORFs were also found to be present in the genomes of phages (Team 1, vB_SauM-fRuSau02, Sb_1 and ISP) that are components of several commercial phage mixtures with reported wide host ranges. This is the first comparative study of therapeutic staphylococcal phages within the recently described genus Kayvirus.